A GENRE-BASED APPROACH TO TEACHING WRITING DISCUSSION TEXT TO SENIOR HIGH SCHOOL STUDENTS - Megani, Irna (2015)
This study aims to investigate the benefits of the genre-based approach (GBA) to teaching writing Discussion text to twelve-graders in one senior high school in Sumedang. The study also investigates students' responses towards the use of the GBA to writing Discussion text. The study employs a case-study design (Cresswell, 2009; Lodico et al, 2010). The data were gained from the teaching program which implemented the GBA to writing Discussion text, students' writing texts, and interview with three students. The data from observation were analyzed based on the implementation of the GBA and students' behavior in the classroom. Moreover, data from students' writing texts were analyzed in terms of the schematic structure and linguistic features using the framework of the SFL GBA (Halliday, 1994; Gerot and Wignell, 1994; Eggins, 2004; Emilia, 2010, 2011, 2012). Finally, the data from the interview were transcribed and analyzed based on several aspects related to the implementation of the GBA. From the classroom observation, it shows that the GBA is beneficial to improve students' practice of writing Discussion text. In addition, students' writing products improved in terms of the schematic structure and linguistic features. Furthermore, the interview results show that the students gave positive responses towards the GBA, especially to the joint construction stage and teacher's feedback. However, some students, especially low-achieving students still need more guidance, improvements, and explicit teaching in modelling stage for the dissatisfactory writing products to allow their improvement writing of the Discussion text. It is suggested that for further studies the implementation of the GBA should be conducted in other contexts and that the GBA should be implemented in Indonesian classrooms since it supports more practice of writing to students in the classroom.;--- Penelitian ini bertujuan untuk mengivestigasi kelebihan dari genre-based approach (GBA)/pendekatan genre-based dalam mengajar menulis teks Discussion pada siswa kelas XII di sebuah sekolah menengah atas di Sumedang. Penelitian ini juga menginvestigasi respon siswa terhadap penggunaan GBA dalam menulis teks Discussion. Penelitian ini menggunakan case study (Cresswell, 2009; Lodico et al, 2010). Data didapatkan dari program mengajar dimana GBA diterapkan dalam menulis teks Discussion, tulisan/teks yang ditulis oleh siswa, dan wawancara dengan tiga orang siswa. Data dari observasi dianalisis berdasarkan penerapan dari GBA dan sikap siswa terhadap penerapan GBA di dalam kelas. Kemudian, data data yang didapat dari teks siswa dianalisis berdasarkan schematic structure dan linguistic features dari teks Discussion dengan menggunakan teori dari SFL GBA (Halliday, 1994; Gerot and Wignell, 1994; Eggins, 2004; Emilia, 2010, 2011, 2012). Data terakhir adalah dari wawancara yang ditulis dan dianalisis berdasarkan beberapa aspek yang berhubungan dengan penerapan GBA di kelas. Hasil observasi dikelas menunjukkan bahwa GBA bermanfaat dalam meningkatkan kemampuan siswa dalam menulis teks Discussion. Kemudian, teks yang ditulis oleh siswa menunjukkan peningkatan berdasarkan dari schematic structure dan linguistic features. Sejauh ini, hasil dari wawancara menunjukkan bahwa siswa memberikan respon yang positif terhadap penerapan GBA, khususnya terhadap joint construction stage dan feedback dari guru. Bagaimanapun juga, beberapa siswa, khususnya siswa dengan kemampuan low-achieving masih membutuhkan bimbingan, peningkatan, dan explicit teaching saat modeling stage untuk meminimalisir hasil yang kurang memuaskan dari hasil teks yang diproduksi oleh siswa. Maka dari itu, untuk penelitian selanjutnya penerapan GBA harus dilakukan dalam konteks yang lain dan GBA harus diterapkan di Indonesia sejak GBA memberi kesempatan kepada siswa untuk 'practice' menulis.